Early Bilateral Cystoid Macular Oedema Secondary to Fingolimod in Multiple Sclerosis - Lei Liu; Fiona Cuthbertson (Case Reports in Medicine)
We report a case of fingolimod-associated bilateral cystoid macular oedema in a patient with multiple sclerosis (MS). A 34-year-old female, diagnosed with MS at age of 30, developed bilateral blurred vision 5 days after initiation of fingolimod. She was misdiagnosed as optic neuritis initially and fingolimod was only discontinued 3 weeks after onset of her visual symptoms when OCT showed prominent bilateral cystoid macular oedema and subretinal fluid. Although her left corrected vision returned to 6/6, she had persistently decreased right visual acuity of 6/12 after 5 months. This paper aims to raise awareness among ophthalmologists and neurologists of the importance of early recognition of macular oedema associated with fingolimod.